Morfologi dan Morfometri Pomacea canaliculata (Gastropoda: Ampullariidae) di Kecamatan Tulangan, Kabupaten Sidoarjo - Dewi Hanuninda; Reni Ambarwati; Dwi Anggorowati Rahayu (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to describe the presence of Pomacea canaliculata in Tulangan District, Sidoarjo Regency, and to identify its morphological and morphometric characteristics. The method used was purposive sampling, with specimens collected from three different locations: Saman Hudi River, Kepatihan Village rice fields, and Kenongo Village rice fields. Morphological observations included shell coiling direction, shell shape and color, aperture shape, umbilicus type, and operculum type. Morphometric measurements covered shell height and width, tentacle length, body whorl height, and aperture height and width. The results showed that Pomacea canaliculata shells are round, with yellowish-brown to dark brown coloration and spiral line patterns following the coiling direction. The aperture is oval to elongated crescent-shaped, slightly widened at the base, with a slit-type umbilicus, and a corneous operculum with concentric rings and a subcentral nucleus. Based on morphometric analysis using Principal Component Analysis (PCA), the largest Pomacea canaliculata individuals were found in Kepatihan Village rice fields, while the smallest were found in Saman Hudi River. Differences in morphology and morphometry among locations indicate significant environmental influences, including habitat conditions and natural selection. Keywords: Ampullariidae, Agricultural Ecosystem, Habitat, Invasive, Characteristics